立位での側方移動と体幹前傾動作に関する筋電図、動作解析から臨床を考える: 股関節周囲筋群に着目して - 清水, 貴史; 村岡, 秀映; 玉置, 昌孝 (関西理学療法, 2019)
In clinical practice, lateral weight shift to one leg in the standing position and trunk anterior tilt movement in the standing position are sometimes recommended for patients for whom movement in the standing position is difficult. It was found that postural changes of the lower limbs affect the activities of lower limb muscles. Because of this finding, it has become necessary to clarify the influence of postural changes on hip muscles. In this paper, we determined the activities of hip extensor muscles when lateral weight shift to one leg in the standing position and trunk anterior tilt movement in the standing position are recommended.